2004
DOI: 10.1177/107906320401600304
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Longitudinal Study of Sexual Recidivism Among Adolescent Sex Offenders

Abstract: This paper reports on a follow-up of a sample of 303 adolescent male sex offenders from New South Wales, Australia. Adult rearrest and reconviction data were obtained for 292 of these individuals. The mean observation period between their adjudication as adolescents and their follow-up as adults was 7.3 years. Seventy-five (25%) received further convictions for sexual offenses prior to their 18th birthday. As adults, 25 (9%) came to the attention of police for further alleged sexual offenses, including 14 (5%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(44 citation statements)
references
References 30 publications
4
37
0
3
Order By: Relevance
“…This hypothesis raises issues about focusing solely on the risk of sexual offending in adulthood as an outcome measure for JSOs. Previous recidivism studies with JSOs have found that if these youth do reoffend, it is most likely a nonsexual crime (e.g., Caldwell, 2002;Hendriks, 2006;McCann & Lussier, 2008;Nisbet, Wilson, & Smallbone, 2004 (81.3%) persisted their nonsexual offending in adulthood. The study, therefore, suggests that an intervention scheme that does not take into consideration both their delinquent involvement and their sexual offending may not have the desired effect in preventing recidivism (also see Hendriks, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis raises issues about focusing solely on the risk of sexual offending in adulthood as an outcome measure for JSOs. Previous recidivism studies with JSOs have found that if these youth do reoffend, it is most likely a nonsexual crime (e.g., Caldwell, 2002;Hendriks, 2006;McCann & Lussier, 2008;Nisbet, Wilson, & Smallbone, 2004 (81.3%) persisted their nonsexual offending in adulthood. The study, therefore, suggests that an intervention scheme that does not take into consideration both their delinquent involvement and their sexual offending may not have the desired effect in preventing recidivism (also see Hendriks, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The present study does not address sexual offender recidivism, as none of the youths had pre-treatment sexual offenses. However, the extant research strongly suggests that youth with sexual behavior problems, including youth with charges for sexual offenses, are unlikely to commit future sexual crimes, particularly when they have completed empirically validated interventions (Borduin, Henggeler, Blaske, & Stein, 1990;Borduin & Schaeffer, 2001;Caldwell, 2002;Letourneau et al, in press;Nisbet, Wilson & Smallbone, 2004;Reitzel & Carbonnell, 2006;Walker, McGovern, Poey, & Otis, 2004;Worling & Curwen 2000). Policies that require lengthy incarceration or residential treatment, that sentence children and adolescents as adults, or that impose postsentence-completion restrictions on children and adolescents (e.g., in the form of indeterminate civil commitment, sex offender registration, and community notification) fail to recognize the tremendous potential of these youths--with the help of their families and evidence-based interventions--to overcome early mistakes and even early but serious criminal acts (Letourneau & Miner, 2005;MacArthur Foundation Research Network on Adolescent Development and Juvenile Justice, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The findings regarding sexual and non-sexual re-offending of JSO-C compared to JSO-A are conflicting and still remain unclear (Hart-Kerkhoffs et al, 2009;Kahn & Chambers, 1991;Nisbet, Wilson, & Smallbone, 2004;Parks & Bard, 2006;Skubic Kemper & Kistner, 2007).…”
Section: Introductionmentioning
confidence: 99%